Biodiversity of lactic acid bacteria isolated from fermented milk products in Xinjiang, China. Issue 2 (3rd April 2019) - Mo, Lanxin; Jin, Hao; Pan, Lin; Hou, Qiangchuan; Li, Chuanjuan; Darima, Iaptueva; Zhang, Heping; Yu, Jie
ABSTRACT: Fermented dairy products have been produced and consumed for thousands of years in Xinjiang, China. In this study, traditional culture-dependent methods and 16S rRNA gene analyses were performed to analyze the composition of lactic acid bacteria (LAB) from 86 samples of traditional fermented dairy products collected from four regions of Xinjiang. Quantitative polymerase chain reaction (qPCR) was used to quantify Bifidobacterium and Lactobacillus species. The LAB isolates ( N = 705) were identified as belonging to seven genera and 26 species or subspecies. The predominant species of all isolates were Lactobacillus ( Lb .) delbrueckii subsp. bulgaricus, Lb. fermentum, and Lb. helveticus . The LAB counts of these samples ranged from 5.35 to 10.06 Log CFU/mL. The bacterial counts of seven lactobacilli species and Bifidobacterium ranged from 0.98 ± 0.14 Log CFU/mL (for Lb. sakei from fermented mare milk) to 9.91 ± 0.17 Log CFU/mL (for Lb. helveticus from fermented mare milk). While the microbiota was significantly different between yak and cow milk, there was no significant difference between the Tex and Zhaosu counties. In conclusion, LAB communities in traditional fermented dairy products are complex and differ among local regions within Xinjiang.